Diagnostic value of the rectal ammonia tolerance test, fasting plasma ammonia and fasting plasma bile acids for canine portosystemic shunting. Issue 3 (June 2015) - van Straten, G.; Spee, B.; Rothuizen, J.; van Straten, M.; Favier, R.P.
Highlights An increase in both FBA and FA is sufficient for diagnosing PSS. A negative ATT rules out PSS in a symptomatic dog. PSS in symptomatic dogs is virtually excluded when FBA is not increased. For screening, FBA alone is sufficient to exclude the presence of PSS. Blood ammonia at 20 min as part of the ATT has no additional benefit.